Value of the toluidine blue test as an aid to determine the biopsy site in actinic prurigo cheilitis - Lily Margoth Cedeño-Suárez; María Elisa Vega-Memije; Juan Carlos Cuevas-González; Adalberto Mosqueda-Taylor (University of São Paulo, 2021)
Actinic prurigo (AP) is a type of photodermatosis that primarily affects the Latin American mestizo population. Histologically, AP cheilitis exhibits acanthosis with spongiosis and vacuolation of the basal cell layer overlying a dense lymphocytic inflammatory infiltrate that forms well-defined lymphoid follicles. Toluidine blue is a thiazide, acidophilic, and metachromatic dye used in vivo to selectively stain the acidic components of tissues such as sulfates, carboxylates, and phosphate radicals that are incorporated into DNA and RNA. It is necessary to develop a method that allows detecting, on clinical grounds the area of the lesion in which it is more feasible to find such structures. Thus to increase the sensitivity of the biopsy, in AP cheilitis to accurately identify where the lymphoid follicles reside, based on the higher concentration of DNA in such structures and thus confirm the diagnosis. In this study, staining was positive in 85% of patients with AP cheilitis, in 14 of whom 82% lymphoid follicles were observed by histopathology. One of the pathologist's problems in establishing the diagnosis of AP is that the main histopathological characteristics are not always identified in the submitted samples because it is not easy to clinically identify the most representative site of the lesion selected for performing a biopsy. Based on our results, we propose using toluidine blue as an auxiliary method to choose a tissue sample to facilitate the diagnosis and allow clinicians to make clinical correlations between the histopathological and therapeutic findings.